Comparison of Oral Azithromycin and Intra Venous Ceftriaxone for Treatment of Uncomplicated Enteric Fever in Children - Imran Khokar, Saba Afzal, Samiya Naeemullah, Imran Khokar, Saba Afzal, Samiya Naeemullah (Journal of Rawalpindi Medical College, 2019)
Background : To compare the clinical efficacy of intravenous (I/V) Ceftriaxone with oral Azithromycin in 2-12 year old children diagnosed with enteric fever. Methods: In this comparative study children with the history of fever for >4 days and at least two out of these findings, i.e., toxic physical appearance, abdominal pain, coated tongue, hepatomegaly, splenomegaly were divided into two equal groups. Patients in Group A were given Azithromycin 20 mg / kg/ day as a single oral dose whereas patients in Group B were given Ceftriaxone 100 mg/kg/day as a single I/V injection for 07 days. Before initiation of therapy samples for Typhidot and Widal test were collected and only those testing positive were included. Results: There were 42 (93.3%) and 40 (88.9%) patients in both the groups respectively who were clinically cured. No significant difference was found between these two groups (p-value 0.459). Conclusion: There was no difference in the clinical efficacy between Ceftriaxone and Azithromycin for the treatment of typhoid fever in children.